Fairness and externalities - Rodrigo A. Velez (Theoretical Economics, 2016)
We study equitable allocation of indivisible goods and money among agents with other-regarding preferences. First, we argue that Foley's (1967) equity test, i.e., the requirement that no agent prefer the allocation obtained by swapping her consumption with another agent, is suitable for our environment. Then, we establish the existence of allocations passing this test for a general domain of preferences that accommodates prominent other-regarding preferences. Our results are relevant for equitable allocation among inequity-averse agents and in a domain with linear externalities that we introduce. Finally, we present conditions guaranteeing that these allocations are efficient.
Keywords: D63; C72; 330; Equity; efficiency; other-regarding preferences; equal income competitive allocations; first welfare theorem